Cellular enhancement of frozen meniscus allograft combining native meniscus and mesenchymal stromal cell injections - Struijk, Caroline; Lydon, Katherine L.; Husen, Martin; Verdonk, Peter; Michielsen, Jozef; van Wijnen, Andre J.; Krych, Aaron J.; Saris, Daniel B.F. (Cartilage, 2025)
Objective - This proof-of-concept study investigated an improved cell-based injection therapy combining mesenchymal stem cells (MSCs) and meniscus cells (MCs) to support superior meniscus allograft repopulation and early revival compared to injecting MSCs alone. - Design - In this controlled laboratory study, frozen meniscus allograft samples were injected vertically with a cell suspension containing different ratios of MSCs and MCs or control (lactated ringers) and cultured for 28 days. Samples were analyzed weekly for cell viability, migration, and metabolism using histological and biochemical assays. Tissue medium was analyzed for matrix metalloproteinase (MMP) expression using zymography. - Results - Cellular repopulation of frozen allografts injected with different cell suspensions was validated by immunohistochemistry. Significant higher DNA content was evidenced in grafts treated with suspensions of MCs or MC:MSC (1:4 ratio). Cell metabolic activity was significantly different between all treated groups and control group after 1 week. Allografts injected with MCs showed significantly more cell proliferation than injections with MSCs. MMP2 activity was detected in medium of all grafts cellularized with MCs with or without MSCs. Scanning electron microscopy (SEM) analysis showed resolution of the needle puncture, but not in the control group. Cell labeling of MCs upon injection of mixed MC:MSC suspensions revealed a gradual increase in the cell ratio. - Conclusions - The findings of this study establish that injection of MCs with or without MSCs enhances the cellularity of meniscus allograft to support early graft revival and remodeling.